Constraining the Accretion Geometry of the Intermediate Polar EX Hya Using NuSTAR, Swift, and Chandra Observations - Luna, Gerardo Juan Manuel (2018)
In magnetically accreting white dwarfs, the height above the white dwarf surface where the standing shock is formed is intimately related with the accretion rate and the white dwarf mass. However, it is difficult to measure. We obtained new data with NuSTAR and Swift that, together with archival Chandra data, allow us to constrain the height of the shock in the intermediate polar EX Hya. We conclude that the shock has to form at least at a distance of about one white dwarf radius from the surface in order to explain the weak Fe Kα 6.4 keV line, the absence of a reflection hump in the high-energy continuum, and the energy dependence of the white dwarf spin pulsed fraction. Additionally, the NuSTAR data allowed us to measure the true, uncontaminated hard X-ray (12-40 keV) flux, whose measurement was contaminated by the nearby galaxy cluster Abell 3528 in non-imaging X-ray instruments.